Auxin and cytokinin mediated regulation involved in vitro organogenesis of papaya. - Zhao, X.; Song, J.; Zeng, Q.; Ma, Y.; Fang, H.; Yang, L.; Yue, J.
In vitro organogenesis is a multistep process which is largely controlled by the balance between auxin and cytokinin. Previous studies revealed a complex network regulating in vitro organogenesis in Arabidopsis thaliana; however, our knowledge of the molecular mechanisms underlying de novo shoot formation in papaya (Carica papaya)remains limited. Here, we optimized multiple factors to achieve an efficient and reproducible protocol for the induction of papaya callus formation and shoot regeneration. Subsequently, we analyzed the dynamic transcriptome profiles of samples undergoing this process, identified 5381, 642, 4047, and 2386 differentially expressed genes (DEGs), including 447, 66, 350, and 263 encoding transcription factors (TFs), in four stage comparisons. The DEGs were mainly involved in phytohormone modulation and transduction processes, particularly for auxin and cytokinin. Of these, 21 and 7 candidate genes involved in the auxin and cytokinin pathways, respectively, had distinct expression patterns throughout in vitro organogenesis. Furthermore, we found two genes encoding key TFs, CpLBD19 and CpESR1, were sharply induced on callus induction medium and shoot induction medium, indicating these two TFs may serve as proxies for callus induction and shoot formation in papaya. We therefore report a regulatory network of auxin and cytokinin signaling in papaya according to the one previously modeled for Arabidopsis. Our comprehensive analyses provide insight into the early molecular regulation of callus initiation and shoot formation in papaya, and are useful for the further identification of the regulators governing in vitro organogenesis.
Keywords: IN VITRO ORGANOGÉNESIS; AUXIN; CYTOKININ; PAPAYA; TRANSCRIPTOME